CRITERIA FOR DEVELOPMENT OF CREATIVE THINKING ABILITY OF PRIMARY CLASS STUDENTS - Zhangil ESHPULATOVA (Scholar Express Journal, 2023)
In this article, concepts about creativity are given, and recommendations are given for the development of creativity in primary school students. Factors, principles and means of improving creative thinking skills of primary school students, ways to control creative thinking skills of primary school students are shown
Keywords: Education; Methodology; Thinking; Creativity